FORMULASI CREAM ANTI AGING DARI EKSTRAK BUAH BIT (Beta vulgaris L) - Harefa, Karnirius; Sitorus, Binsar; Christiani N Daely, Ruth; Fikrih Utama, Rezza (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
Anti-aging is a process to prevent or slow down the effects of aging so that a person becomes fresher, more beautiful, and more youthful. Beet fruit a function as an antioxidant to protect against the effects of sunlight, compounds that have anti-oxidant activity in beets include betacyanin and vitamin C, and betacyanin is a substance that can neutralize free radicals. often used is in the form of face cream where its functions include cleaning, and refreshing, and the presence of beetroot extract also adds to its function as a protector and adds nutrition, especially to regenerate facial skin. This research uses experimental methods which include making cream preparations and testing cream preparations against anti-aging activity on the skin. The sample in this study used beetroot ethanol extract obtained from Medan City and 12 respondents who were used as panels in the anti-aging activity test. The results of this study showed that the physical quality test of the cream preparation was homogeneous, remained stable in storage for 4 weeks, was an oil-in-water (m/a) emulsion type, had a pH of 6.1–6.6 and did not irritate the skin. In the anti-aging test at week four the blank cream showed increased results with a percent recovery of 30.83%, the comparison cream showed increased results with a percent recovery of 60%, cream 5% showed increased results with a percent recovery of 41.49% lower than cream In comparison, 10% cream showed an increase in the percentage of recovery 59.61 lower than the comparison cream and 15% cream showed an increase in the percentage of recovery 61.55% higher than the comparison cream. The conclusion of this study is that the ethanol extract of beetroot can be formulated into a cream preparation with an oil-in-water emulsion type, the ethanol extract of beetroot has the best anti-aging activity at 15% cream and the lowest is 5% cream.